ANALISIS PENERAPAN DAN PENGUATAN HUKUM ANIMAL WELFARE PADA BISNIS SAPI DI INDONESIA - hidayat, rahmat (Magister Ilmu Hukum Sekolah Pascasarjana Unida, 2015)
Cattle trading is a complex process from farm to consuments. The main issue in cattle farming is animal welfare and its treatment, such as a case of slaughterhouse and Eid al-Adha phenomenon in Indonesia. The objectives of this research are to analyse the treatment and principles of animal welfare in cattle trading, also to create a model for animal welfare for religious offering. This research is a normative one that is supported by empirical study. Data collection is using literature study (main data) and quesionare for additional data. The results of the research showed that animal welfare at cattle trading in Indonesia has not a good reputation according to the applicable law, so that we need a veterinary authority board to support animal welfare laws. A model for animal welfare for religious offering can be created by integrating animal market with slaughterhouse, using health and eco-green concepts, application of technology information for marketing strategy, and improvement legal structure.